Assessment of Murabaha Financing Products of Ja’iz Bank Based on Maqasid Al-shari’ah Framework (Journal of Management and Social Sciences, 2025)
Islamic Banks offer various banking products and services with different features to meet the different needs of the customers. Yet, the Islamic banking products offered by the Islamic banks must be in line with the Shari’ah objectives (Maqasid al-Shari’ah) which are centralised on the objectives of accomplishing the development of both the spiritual and socio-economic well-being. This research was undertaking to assess the ability of Murabaha Financing Products to meet of with Maqasid al-Shari’ah in Ja’iz bank plc. The study adopted quantitative survey method and a sample of (382) respondents were selected from the population of 75088 from the four branches of customers of Jaiz bank in Kano State using a stratified sampling technique. The questionnaire was administered to the respondents through a hand-to-hand distribution method, with the assistance of trained research assistants. The respondents were accessed directly at various branches of Jaiz bank within the study area. The specific measures of the Shari’ah objectives are customer welfare promotion, transfer of property rights, and right of ownership. Descriptive statistic was applied in this research to find out if Murabaha financing products transacted in the light of Maqasid al-Shari’ah in Ja’iz Bank Plc or not. Finding from the study reveals that the major objectives of Shari’ah are addressed in the transaction of the Murabaha products. The study therefore recommended that Jaiz Bank should maintain its focus on promoting customer welfare through its Murabaha financing products and The Jaiz bank should ensure transparency in its financing practices, particularly in contract terms and profit margins.Keywords:Assessment, Murabaha, Financing, Maqasiq al-Shari’ah and Ja’iz Bank